Adaptive sliding mode enhanced disturbance observer-based control of surgical device. (July 2019) - Lau, Jun Yik; Liang, Wenyu; Tan, Kok Kiong
Abstract: This paper presents an enhanced adaptive robust disturbance observer-based motion tracking control methodology. This control approach is established and investigated for a semi-automated hand-held ear surgical device for the treatment of Otitis Media with Effusion. The proposed control methodology is utilised for tracking a desired motion trajectory in the presence of unknown or uncertain system parameters, nonlinearities including hysteresis, and disturbances in the motion system. The stability of the control approach is analysed. The convergence of position and velocity tracking errors is proven theoretically. A precise tracking performance following desired motion trajectory is demonstrated in the experimental study. Highlights: An adaptive robust motion controller is proposed for a PUA-based surgical device. A combination of an adaptive technique, a sliding mode control scheme, a DOB is used. An advanced DOB which can simplify the system identification process is implemented. Only the estimated system parameters are required by using this approach. Acceleration measurement is not required by using this approach in actual realisation. Precise motion tracking performance and good robustness can be achieved.